PERBANDINGAN DAYA DUKUNG PONDASI AKIBAT PERBEDAAN METODE KONSTRUKSI PONDASI DALAM - Budijanto Widjaja; Sri Ratna Wahyuningsih (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2017)
This research uses 4 types of piles as the objects, a bored pile, a continuous flight auger (CFA) pile, a full displacement pile (FDP), and a full displacement pile with an expander body, the depth for all piles is 9.5 m. The bored pile, CFA, FDP, and FPD with expander body have the following diameter: 62 cm, 45 cm, 45 cm, and 22 cm. Each pile, which has different construction method, is tested by full-scale static loading, excluding the FDP with expander body, it uses Osterberg-Cell. The research aims to know which analysis method best suits a particular kind of foundation and to compare each pile capacity. The pile capacity analysis conventionally using t-z and q-z curve gives 13%-15% higher estimation than the static loading test result. Analysis using Plaxis for FDP with expander body gives lower estimation than the Osterberg Cell test result. Keywords: Continuous flight auger, full displacement pile, t-z curve, q-z curve